2019
DOI: 10.7717/peerj.6125
|View full text |Cite
|
Sign up to set email alerts
|

Defensin-like peptides in wheat analyzed by whole-transcriptome sequencing: a focus on structural diversity and role in induced resistance

Abstract: Antimicrobial peptides (AMPs) are the main components of the plant innate immune system. Defensins represent the most important AMP family involved in defense and non-defense functions. In this work, global RNA sequencing and de novo transcriptome assembly were performed to explore the diversity of defensin-like (DEFL) genes in the wheat Triticum kiharae and to study their role in induced resistance (IR) mediated by the elicitor metabolites of a non-pathogenic strain FS-94 of Fusarium sambucinum. Using a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 73 publications
0
33
0
3
Order By: Relevance
“…Spinach homologs of those genes encoding plant defensin-like proteins were also strongly expressed during the incompatible interaction, indicating their involvement in defense in this interaction. A number of studies have shown the inhibitory effect of plant defensin peptides to various fungal and bacterial pathogens [69][70][71][72] . Genes encoding ACC oxidase homologs in spinach were up-regulated across the infection times in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Spinach homologs of those genes encoding plant defensin-like proteins were also strongly expressed during the incompatible interaction, indicating their involvement in defense in this interaction. A number of studies have shown the inhibitory effect of plant defensin peptides to various fungal and bacterial pathogens [69][70][71][72] . Genes encoding ACC oxidase homologs in spinach were up-regulated across the infection times in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Plant defensins are induced as a part of the systemic defense response during pathogenic attack and environmental stresses, and defensin genes respond to some signalling molecules, including MeJA, ETH, and SA. After inoculation with F. oxysporum, many DEFLs show enhanced expressions in induced resistancedisplaying wheat seedlings (Odintsova et al 2019). The OsDEF expressions are highly induced by Aspergillus oryzae infection (Weerawanich et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 13 defensin genes have been identified in the Arabidopsis thaliana genome (Thomma et al 2002), and also 317 DEFLs (Silverstein et al 2005). In total, 93, 79, and 143 DEFL genes have been characterized in rice (Oryza sativa), grapevine (Vitis vinifera), and wheat (Triticum kiharae), respectively (Silverstein et al 2007, Giacomelli et al 2012, Odintsova et al 2019. In addition, the DEFLs have the hallmarks of defensin genes, including the conserved cysteine residues, CSαβ motif or γ-core motif (Silverstein et al 2005, Giacomelli et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that there exists significant association between amino acid metabolism and plant resistance to pathogens (Frerigmann et al., 2016; Stuttmann et al, 2011). Amino acids are not only precursors for defensive antimicrobial compounds but also can directly affect plant resistance to specific pathogens (Odintsova et al, 2019; Stuttmann et al., 2011). Pipecolic acid (Pip), a lysine‐derived non‐protein amino acid, has important functions in both plants and animals (Vranova, Lojkova, Rejsek, & Formanek, 2013; Xu et al., 2018; Yuan et al., 2017).…”
Section: Introductionmentioning
confidence: 99%